AgNOR polymorphism association with squamous intraepithelial lesions and invasive carcinoma with HPV infection Asociación de los polimorfismos AgNORs con lesiones intraepiteliales escamosas, carcinoma cervical e infección por VPH - Luz del Carmen Alarcón-Romero; Berenice Illades-Aguiar; Eugenia Flores-Alfaro; Marco Antonio Terán-Porcayo; Verónica Antonio-Véjar; Elba Reyes-Maldonado (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: Evaluate the relationships between AgNORs polymorphisms and squamous intraepithelial lesions (SIL) and squamous cell carcinoma (SCC) with HPV infection. MATERIALS AND METHODS: A study was carried out on sixty women from the state of Guerrero, Mexico. HPV detection was performed by PCR. AgNORs were identified by argentic impregnation. One hundred cells per slide were counted and classified according to the polymorphism of AgNORs dots; typical (spherical) and atypical (large, kidney-shaped and clustered). RESULTS: A total of 100% of the cases were positive for HPV infection. Nine different high-risk HPV genotypes were found, type16 was the most common (48.6%). The AgNORs showed a significant decrease in spherical shape according to neoplastic development. The three atypical shapes showed a significant increase in SIL and SCC (p-trend<0.001). CONCLUSIONS: AgNORs polymorphism rises progressively according to the grade of histological lesions that can be useful as a prognosis for progression of SCC. OBJETIVO: Evaluar la relación entre los polimorfismos de AgNORs con las lesiones intraepiteliales escamosas (LIE) y carcinoma de células escamosas (CCE). MATERIAL Y MÉTODOS: Se estudiaron sesenta mujeres del estado de Guerrero, México. La detección del VPH fue por PCR y los AgNORs por impregnación argéntica; se contaron 100 células y se clasificaron por tipo de polimorfismo de AgNORs: típico (esférico) y atípicos (largo, forma de riñón o de racimo). RESULTADOS: El 100% de los casos presentaron infección por VPH, se encontraron nueve genotipos diferentes de VPH de alto riesgo, el 16 fue el más común (48.6%). La forma esférica de los polimorfismos de AgNORs mostró una disminución con el desarrollo neoplásico y las atípicas incrementaron progresivamente con SIL y SCC (p-tendencia<0.001). CONCLUSIONES: Los polimorfismos AgNORs se incrementan progresivamente con el grado de lesión histológica, y pueden ser útiles en el pronóstico de progresión del carcinoma cervical.